CO2 outgassing during collisional orogeny is facilitated by the generation of immiscible fluids - Chiara Groppo; Franco Rolfo; Maria Luce Frezzotti (Communications Earth & Environment, 2022)
Outgassing of CO2 during collisional orogeny can be explained by the generation of immiscible CO2-rich fluids and hydrosaline brines in metamorphosed sediments, according to thermodynamic modelling applied to the Himalaya.